2011
DOI: 10.1128/aem.05577-11
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Differences between the Communities of Arbuscular Mycorrhizal Fungi Colonizing Galls and Roots of Prunus persica Infected by the Root-Knot Nematode Meloidogyne incognita

Abstract: Arbuscular mycorrhizal fungi (AMF) play important roles as plant protection agents, reducing or suppressing nematode colonization. However, it has never been investigated whether the galls produced in roots by nematode infection are colonized by AMF. This study tested whether galls produced by Meloidogyne incognita infection in Prunus persica roots are colonized by AMF. We also determined the changes in AMF composition and biodiversity mediated by infection with this root-knot nematode. DNA from galls and root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 31 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Glo G3 was the most frequent and abundant OTU in both terrestrial and epiphytic root samples. In previous research conducted in other Mediterranean semiarid environments, this OTU was also the most abundant in the roots of the analyzed plants (32,33). Hence, Glo G3 appears to be an AMF of great plasticity that is well adapted to the environmental conditions prevailing in semiarid areas and which shows the ability to colonize many different plant species and contrasting habitats.…”
Section: Discussionsupporting
confidence: 49%
“…Glo G3 was the most frequent and abundant OTU in both terrestrial and epiphytic root samples. In previous research conducted in other Mediterranean semiarid environments, this OTU was also the most abundant in the roots of the analyzed plants (32,33). Hence, Glo G3 appears to be an AMF of great plasticity that is well adapted to the environmental conditions prevailing in semiarid areas and which shows the ability to colonize many different plant species and contrasting habitats.…”
Section: Discussionsupporting
confidence: 49%
“…For sedentary endoparasitic nematodes, Dos Anjos et al (2010) showed that M. incognita could negatively affect the sporulation of the AMF Scutellospora heterogama in sweet passion fruit, while Alban et al (2013) found that pre-inoculation of M. exigua led to a significant increase in the subsequent colonization of AMF compared to uninoculated mycorrhizal plants. del Mar Alguacil et al (2011) also reported that the highest AMF diversity was found in uninfected roots compared to M. incognita infected roots and galls, and that the composition of the AMF community was different between infected and uninfected roots. Their results indicate that AMF colonization might also be suppressed by PPN, depending on the AMF species as some AMF species were not affected by the PPN.…”
Section: Direct Competition For Nutrients and Spacementioning
confidence: 93%
“…Cyst nematode feeding cells, the so-called syncytia, are confined within the endodermis and should therefore be less affected by AMF. Through PCR and DNA sequencing, del Mar Alguacil et al (2011) reported that galls produced by M. incognita in Prunus persica roots could be colonized by AMF. However, as mycorrhizal arbuscules are short-lived structures ( Parniske, 2008 ; Javot et al, 2011 ), it is difficult to distinguish whether AMF or PPN colonized the same root part first.…”
Section: Direct Competition For Nutrients and Spacementioning
confidence: 99%
“…Other beneficial effects of AMF are plant growth promotion [2], increased tolerance of drought [3], heavy metals [4] and plant protection agents [5]. In fact, in a previous study carried out at the site that is also the subject of the current work [6], it was found that galls produced in Prunus persica roots due to infection with Meloidogyne incognita were extensively colonized by AMF, whose function might be to act as protection agents against opportunistic pathogens. Furthermore, the diversity of AMF influences a number of important ecosystem processes, including plant productivity, plant diversity and soil structure [7], [8], [9].…”
Section: Introductionmentioning
confidence: 81%